Molecular analysis for the OprD gene among Pseudomonas aueroginosa clinical isolates obtained from hospitals in Jordan - Khalid M Abu Khadra; Safa’a Y Al-Rabaia; Ahmad M Khalil; Luay F Abu-Qatouseh; Mahmoud J Abussaud (Journal of Infection in Developing Countries)
Introduction: Pseudomonas aeruginosa has increasingly been associated with the emergence of antibiotic resistance. Antibiotic resistance among P. aeruginosa isolates is an ambiguous and complicated mechanism utilizing several enzymes and structural proteins. This study was conducted to investigate the prevalence of mutations in the chromosomal OprD gene that show resistance to carbapenems among clinical isolates of P. aeruginosa.